2007
DOI: 10.1111/j.1365-2230.2007.02512.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida spp. colonization and serum anticandidal antibody levels in patients with chronic urticaria

Abstract: Intestinal and oral colonization of Candida spp. and serological evidence of Candida infections were not significantly different between patients with CU and controls. Claims of triggering of CU by Candida spp. should be explored in studies that measure allergic reactivity to Candida, and also in those that include eradication therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
1
10
0
6
Order By: Relevance
“…Occult infections have been associated with chronic urticaria 9. These include viral, bacterial and parasite infections (including Helicobacter pylori ), which should be treated appropriately, but our patient did not show any infections 1012…”
Section: Discussionmentioning
confidence: 65%
“…Occult infections have been associated with chronic urticaria 9. These include viral, bacterial and parasite infections (including Helicobacter pylori ), which should be treated appropriately, but our patient did not show any infections 1012…”
Section: Discussionmentioning
confidence: 65%
“…Bowel parasites, a rare possible cause of CSU in developed industrial countries, should be eliminated if indicated . In the past, intestinal candidiasis was regarded as a highly important underlying cause of CSU, but more recent findings fail to support a significant causative role . Apart from infectious diseases, chronic inflammatory processes due to diverse other diseases have been identified as potentially triggering CSU.…”
Section: Management Of Urticariamentioning
confidence: 99%
“…Intestinal and oral colonization of Candida spp. and serological evidence (ELISA anti-Candida-IgG/-IgM/-IgA) of Candida infections were not significantly different between patients with chronic urticaria (n = 38) and controls (n = 42) [43]. In contrast, anti-Candida-IgE was found in another study [44].…”
Section: Introductionmentioning
confidence: 99%